Soil-Derived Inocula Enhance Methane Production and Counteract Common Process Failures During Anaerobic Digestion - Mutschlechner, Mira; Praeg, Nadine; Illmer, Paul (Frontiers in Microbiology, 2020)
Although soil-borne methanogens are known to be highly diverse and adapted to extreme environments, their application as potential (anaerobic) inocula to improve anaerobic digestion has not been investigated until now. The present study aimed at evaluating if soil-derived communities can be beneficial for biogas (methane, CH4) production and endure unfavorable conditions commonly associated with digestion failure. Nine study sites were chosen and tested for suitability as inoculation sources to improve biogas production via in situ measurements (CH4 fluxes, physical and chemical soil properties, and abundance of methanogens) and during a series of anaerobic digestions with a) combinations of both sterile or unsterile soil and diluted fermenter sludge, and b) pH-, acetate-, propionate-, and ammonium-induced disturbance. Amplicon sequencing was performed to assess key microbial communities pivotal for successful biogas production. Four out of nine tested soil inocula exerted sufficient methanogenic activity and repeatedly allowed satisfactory CH4/biogas production even under deteriorated conditions. Remarkably, the significantly highest CH4 production was observed using unsterile soil combined with sterile sludge, which coincided with both a higher relative abundance of methanogens and predicted genes involved in CH4 metabolism in these variants. Different bacterial and archaeal community patterns depending on the soil/sludge combinations and disturbance variations were established and these patterns significantly impacted CH4 production. Methanosarcina spp. seemed to play a key role in CH4 formation and prevailed even under stressed conditions. Overall, the results provided evidence that soil-borne methanogens can be effective in enhancing digestion performance and stability and, thus, harbor vast potential for further exploitation.